Prison nursing and its training - M. Sánchez-Roig; A. Coll-Cámara
The main task of nurses is to take care of sick and healthy people and evaluate changes in their health conditions. The goal is to take the appropriate measures to help their recovery or guarantee a dignified death, and if possible, help them regain autonomy and independence. Nursing is present in different areas: primary health, mental health, accident and emergencies, intensive and coronary care, surgical care, paediatrics, geriatrics, public health, occupational health, teaching, etc. In our case, prison nursing, one of the least known branches of the profession, we wanted to investigate more deeply the work of nurses in prisons, which aspect of health care they are responsible for and to what type of population they are geared towards, as well as the necessary training to be able to work in such a particular environment. To conclude, we have seen that university degrees in general nursing do not include knowledge in this area, and that authors from different countries support the specialization of prison nursing and the need for nurses to be trained according to the health conditions of inmates and the characteristics of prisons.